PREPUTIOPLASTY TECHNIQUE AND TIP URETHROPLASTY IN PROXIMAL HYPOSPADIAS - Kumar, Vikash; Kumar, Rajesh (Student’s Journal of Health Research Africa, 2023)
Introduction: Researchers describe a novel procedure for the reconstruction of the prepuce in a cohort of patients who were either circumcised as children or were born with a short prepuce. This study aimed to evaluate the efficacy and feasibility of “tubularized incised plate” (TIP) urethroplasty and “preputial reconstruction” among patients with “proximal hypospadias” and “ventral penile curvature (VPC)”. Methods: Retrospective evaluation of 81 patients with “proximal hypospadias” who had undergone TIP preputioplasty. “Ventral curvature (VC)” was rectified by mobilizing the urethral plate (UP) with the proximal urethra and corpus spongiosum; depending on curvature severity, dorsal plication was also performed. Preputial reconstruction comprised a standard three-layer repositioning of the dorsal hood’s margins. Results: Patients were more than 10 months old and less than 21 years old, with an average of 6 years. Mild curvature (30 cases), moderate curvature (39 cases), and severe curvature (12 cases) were corrected by mobilization of the spongiosum and UP in 42 patients. In addition, 6 patients needed a single-stitch dorsal plication, and 33 cases required mobilization of the proximal urethra. 6 patients and 3 patients had fistula in the urethra and dehiscence of the perpuce respectively. Conclusion: In “proximal hypospadias”, preputioplasty and TIP is feasible without increasing the complication rate. The evaluation of the adequacy of the epidermis of the prepuce using three stay sutures can prevent postoperative phimosis. Recommendations: It is strongly recommended that babies with hypospadias are not circumcised as the foreskin is frequently needed during the operation.